An in situ rewritable electrically-erasable photo-memory device for terahertz waves. Issue 5 (27th January 2020) - Xiong, Luyao; Liu, Bin; Liu, Dandan; Lv, Longfeng; Hou, Yanbing; Shen, Jingling; Zhang, Bo
Abstract : A terahertz read-only in situ electrically-erasable rewritable photo-memory device based on a perovskite:Ag (perovskite with Ag nanoparticles added)/SnO2 /PEDOT:PSS hetero-junction structure is reported. Abstract : A terahertz read-only in situ electrically-erasable rewritable photo-memory device based on a perovskite:Ag (perovskite with Ag nanoparticles added)/SnO2 /PEDOT:PSS hetero-junction structure is reported. Under low optical excitation, considerable terahertz amplitude modulation in a perovskite:Ag/PEDOT:PSS hybrid structure was achieved. When a SnO2 nanoparticle film was inserted between the perovskite and PEDOT:PSS layer, the attenuation of the terahertz signal was weaker than that of the perovskite:Ag/PEDOT:PSS hybrid structure; however, the SnO2 nanoparticle film considerably prolonged the recovery time of the modulated terahertz wave in air after photo-excitation was stopped. In addition, when bias voltages were applied to the perovskite:Ag/PEDOT:PSS and perovskite:Ag/SnO2 /PEDOT:PSS hybrid structures, respectively, the terahertz signals recovered rapidly for both structures. Consequently, the photo-memory functionality was achieved based on a perovskite:Ag/SnO2 /PEDOT:PSS hybrid structure with an in situ method for erasing stored information.